Beamstrahlung backgrounds in ILD at linear (ILC) and circular (FCCee) colliders* - Jeans Daniel (EPJ Web of Conferences, 2024)
We describe a simulation study of backgrounds in the Time Projection Chamber of the International Large Detector due to beamstrahlung, comparing FCC-ee operating at 91 and 240 GeV with ILC at 250 GeV. This background depends on the amount of initial beamstrahlung per bunch crossing, the design of the machine-detector interface, and the collision rate, which are all significantly different at these different colliders. We also estimate the density of the ion cloud which builds up in the TPC due to this background source.